Spatial and temporal changes of urban forest in Jeli, Kelantan. Issue 1 (August 2021) - Baharudin, N Z; Nor, A N M; Nawawi, S A; Aziz, H A; Jamil, R M; Ibrahim, N; Rafaai, N H
Abstract: The rapid growth of urban development in a country affects vegetation and ecosystem area. Nowadays, Jeli was facing the fact of losing its forest cover that had been a substitute with other purposes such as plantation and development. Therefore, this study was conducted to classify the land use change of Jeli and analyze the urban forest changes of Jeli in year 1994, 2006 and 2018. In this study, three satellite images of the study area in year 1994, 2006 and 2018 were processed and analyzed using Remote sensing and Geographical Information System (GIS). The landscape patterns were analyzed using landscape metrics that were calculated by FRAGSTATS software. The analysis showed that the largest patch index (LPI) of Jeli in 2006 is higher, with 66.32% compared to the year 1994 (60.86%) and 2018 (65.44%). The mean patch area (MPA) decreases throughout the year with 5.96 ha, 4.27 ha and 3.97 ha, respectively. The higher of LPI and increase of MPS indicating that the patches is become fragmented. Moreover, the Euclidean nearest neighbor (ENN) value increased from year 2006 to year 2018, from 93.91 m to 109.42 m indicating that the distance patches is increased. The ANOVA test conducted within ENN and AREA's value shows that the ENN value of year 1994 is more significant (p < 0.05) compared to year 2006 and 2018. Oppositely, the AREA's value was found significant for year 2006 and 2018. The results show that the green cover class was increased through years due to the changes of land use purpose where the land use such as vegetation and cleared land classes were replaced with green cover. The outcomes from this study can be used to construct and improve a new and existing landscape planning by the decision-makers, stakeholders and sustainable planners.